Strengthening the role of community pharmacy in HPV vaccination roll-out in Serbia at national and local levels: A pharmacy-based education approach - Ivana Rapajić-Moran; Brankica Filipić; Dragana Rajković; Milan Rakić; Dragana Stojiljković; Bojana Letić; Jasna Urošević; Nataša Bogavac-Stanojević (PLoS ONE, 2025)
Cervical cancer is a significant public health concern in Serbia, with high morbidity and mortality rates (27 and 14.2 per 100,000 women, respectively in 2020). The primary cause of cervical cancer is human papillomavirus (HPV) infection, and HPV vaccination has proven to be an effective prevention strategy. This publication discusses the implementation of the first pharmacy-based education (PBE) program realized through the project of Pharmaceutical Chamber of Serbia – “Ask me about HPV” which aimed at raising awareness of the general population about the importance of HPV vaccination. The program aimed to strengthen the role of community pharmacists in the HPV vaccination roll-out. A total of 250 pharmacists were selected and trained to provide information on HPV infection and promote vaccination uptake. The program aimed to counsel and to educate young adults and parents/guardians. A total of 24,327 subjects were educated during the program’s implementation from February to May 2023, young adults (N=11,313) and parents/guardians (N=13,014). Data showed that only 4.9% of young adults and 6.4% of children (of the parents/guardians surveyed) in Serbia are vaccinated against HPV. The questionaries of 1,387 subjects already vaccinated were excluded from the further analysis and final analysis was performed based on the counseling of 22,941 participants. A significantly higher percentage of parents/guardians stated that they would have their children vaccinated against HPV after counseling at the pharmacy than young adults (42.3% and 34.1% respectively). On the other hand, of those respondents who stated they would get vaccinated after consulting at the pharmacy, a significantly higher number of young adults (51%), compared to parents/guardians (48%), would receive the vaccine specifically at the pharmacy. The results of the project indicate that education of the general population on the benefits of HPV vaccination is highly needed. The expected outcomes of this educational program are increased awareness of the burden of illness, improved consumer education, the potential for higher vaccination rates, and consequently a reduction in cervical cancer incidence and mortality in Serbia.